Description of Stress and Coping Mechanism Farmer in Kalisat District Jember City - Ananda Patuh; Emi Wuri Wuryaningsih; Alfid Tri Afandi (Nursing and Health Sciences Journal (NHSJ), 2021)
Farmers have high risk to suffer psychological health pressure. The factors that cause farmers have psychological pressure are limited land, the decrease of soil fertility, soil degradation, and natural causes. Farmers with high psychological health pressure can suffer stress. This research aims to investigate the representation of Stress and Farmers’ Coping Mechanism in Kecamatan Kalisat Kabupaten Jember. The type of this research was descriptive and simple random sampling was chosen to collect the data sampling technique. 100 farmers were collected. The respondents were measured by using farmers’ stress questionnaire and Brief farmers’ coping mechanism questionnaire COPE. The result of stress representation and farmer’s coping mechanisme analysis showed that the number of farmer’s stress tend to be cognitive response. Meanwhile, the result of coping mechanism showed that most of farmer’s coping mechanism more focus on emotion rather than problem. Test the validity of the stress questionnaire obtained r table = 0.497 with α = 0.05 and reliability of 0.703. Whereas for the coping mechanism α = 0.05 questionnaire, the validity of r table 0.361 and the reliability of 0.778 were obtained. Ethical tests were carried out in this study at the Faculty of Dentistry, Jember University No. 465 / UN25.8 / KEPK / DL / 2019.The result of this study can be a reference for nurses and primary health care service to diagnose farmers’ health diseases especially psychological diseases such as stress and coping mechanism. Nurses can do a preventive efforts, intervention, and health education about factors and symptoms of stress and coping mechanism to the farmers.